Climate change resilience of school premises in Cyprus: An examination of retrofit approaches and their implications on thermal and energy performance. (December 2021) - Heracleous, C.; Michael, A.; Savvides, A.; Hayles, C.
Abstract: Educational buildings form a significant part of non-residential buildings that are of public use, and, in the case of Cyprus, this building stock tends to be less energy-efficient compared to a number of other public building typologies. Moreover, it is the purpose, frequency of use and user density of these buildings that make them a special case for study. These buildings are no longer fit for their assigned purpose as they require significant energy for heating in the winter and cooling in the summer, to avoid overheating. These conditions cause significant concerns in school buildings in Cyprus and the effects of climate change exacerbates these parameters. This research aims to evaluate the effectiveness of different retrofitting measures and their impact on the thermal comfort and the energy performance of educational premises under different climatic scenarios. For the purposes of this study, a secondary school building was selected as a representative case study of educational buildings in Cyprus and was modelled using IES-VE. Retrofit measures optimizing geometry, construction and operation were examined using a calibrated dynamic thermal simulation model in current and future climatic scenarios, to determine both their effectiveness in minimizing heating demand in the winter and overheating conditions in the summer period. Comfort conditions were assessed with reference to international standards based on adaptive thermal comfort. The study demonstrates that most educational buildings in Cyprus cannot ensure thermal comfort conditions, without the support of technical systems, neither in the present nor in anticipated future climatic conditions, thereby indicating the urgent need to take action. According to the research results, natural ventilation and insulation of the roof are considered very important in achieving this goal, as they have the potential to minimize the cooling degree hours by 96.8% and the heating degree hours by 4.3%. A combination of all passive measures and heat recovery ventilation can reduce degree hours for both heating and cooling by 51% in the current climatic conditions, and by 60% and 66.4% according to climatic projections for 2050 and 2090, respectively. The methodology for the evaluation of the thermal and energy behaviour of the educational building stock applied in this study could be a trustworthy tool for decision-making in energy retrofitting projects in Cyprus, as well as in other areas with similar climatic conditions. Highlights: TMY and climate change in 2050 and 2090 were analysed in schools of Southern Europe Thermal comfort and energy performance of classrooms were simulated for A1B scenario The study is a trustworthy tool for decision-making in energy retrofitting projects The need for adaptation is becoming increasingly urgent Mild retrofitting measures can maintain overheating only in the current conditions